2023
DOI: 10.1088/1748-9326/acd1a2
|View full text |Cite
|
Sign up to set email alerts
|

Modification of exploration of long‐term nutrient trajectories for nitrogen (ELEMeNT-N) model to quantify legacy nitrogen dynamics in a typical watershed of eastern China

Abstract: Legacy nitrogen (N) is recognized as a primary cause for the apparent failure of watershed N management strategies to achieve desired water quality goals. The ELEMeNT-N (Exploration of Long‐Term Nutrient Trajectories for Nitrogen) model, a parsimonious and process-based model, has the potential to effectively distinguish biogeochemical and hydrological legacy effects. However, ELEMeNT-N is limited in its ability to address long-term legacy N dynamics as it ignores temporal changes in soil organic N (SON) miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Ballard et al (2019) suggested that recovery time scales simulated by ELEMeNT in the Mississippi River Basin are highly uncertain. Additionally, ELEMeNT outputs for the Mississippi River Basin seem to greatly deviate from other ELEMeNT applications in the Chesapeake Bay and China (Chang et al, 2021; Zhou et al, 2023). Generally, DLEM‐simulated N results are squaring more with the 5–15 year response time reported by Chang et al (2021), Dupas et al (2020), and Stackpoole et al (2021).…”
Section: Resultsmentioning
confidence: 89%
“…Ballard et al (2019) suggested that recovery time scales simulated by ELEMeNT in the Mississippi River Basin are highly uncertain. Additionally, ELEMeNT outputs for the Mississippi River Basin seem to greatly deviate from other ELEMeNT applications in the Chesapeake Bay and China (Chang et al, 2021; Zhou et al, 2023). Generally, DLEM‐simulated N results are squaring more with the 5–15 year response time reported by Chang et al (2021), Dupas et al (2020), and Stackpoole et al (2021).…”
Section: Resultsmentioning
confidence: 89%